Identification of Viral Signatures Using High-Throughput Sequencing on Blood of Patients With Kawasaki Disease - L'Huillier, Arnaud G.; Brito, Francisco; Wagner, Noemie; Cordey, Samuel; Zdobnov, Evgeny; Posfay-Barbe, Klara M.; Kaiser, Laurent (Frontiers in Pediatrics, 2019)
Aims. Kawasaki disease is an acute pediatric vasculitis whose etiology remains unknown but epidemiology and clinical presentation suggest a viral etiology. We performed unbiased high-throughput-sequencing on blood of patients with Kawasaki Disease (KD). Materials and methods. High-throughput-sequencing was performed directly on plasma of children with typical KD. Sequences were aligned against a database of clinically relevant viruses. Results. Four patients were acutely infected in the blood, with respectively poliovirus (vaccine strain), measles (vaccine strain), rhinovirus and bocavirus. Patients with poliovirus and measles had received oral polio and measles vaccines respectively twelve and two weeks prior. Conclusion. Viral signatures were identified in more than half of the patients, including some corresponding to their vaccinal history. This could suggest a temporal association with KD.